Hemostasis in Pediatric Cardiac Surgery - Ravn, Hanne Berg (Seminars in Thrombosis and Hemostasis, 2017)
The majority of children undergoing pediatric cardiac surgery with cardiopulmonary bypass require transfusion of blood products. The management of hemostasis in the pediatric population is challenging, partly due to pronounced alterations in several hemostatic parameters following cardiopulmonary bypass. Despite these marked changes being seen quite often, they are not necessarily an indication for hemostatic interventions. This review summarizes and discusses the available monitoring tests of hemostatic impairment during and following pediatric cardiac surgery. It covers standard laboratory tests, viscoelastic test, evaluation of platelet function, fibrinolysis, and the management of anticoagulation including its reversal. Interpretation of hemostatic measurements is done with due respect to the concept of developmental hemostasis, but also cyanotic heart disease, which are considered by some to be associated with an increased risk of bleeding.
Keywords: pediatric; cardiac surgery; cardiopulmonary bypass; point-of-care tests; developmental hemostasis